High fidelity sensory-evoked responses in neocortex after intravenous injection of genetically encoded calcium sensors - Leikvoll, Austin; Kara, Prakash (Frontiers in Neuroscience, 2023)
Two-photon imaging of genetically-encoded calcium indicators (GECIs) has traditionally relied on intracranial injections of adeno-associated virus (AAV) or transgenic animals to achieve expression. Intracranial injections require an invasive surgery and result in a relatively small volume of tissue labeling. Transgenic animals, although they can have brain-wide GECI expression, often express GECIs in only a small subset of neurons, may have abnormal behavioral phenotypes, and are currently limited to older generations of GECIs. Inspired by recent developments in the synthesis of AAVs that readily cross the blood brain barrier, we tested whether an alternative strategy of intravenously injecting AAV-PHP.eB is suitable for two-photon calcium imaging of neurons over many months after injection. We injected C57BL/6J mice with AAV-PHP.eB-Synapsin-jGCaMP7s via the retro-orbital sinus. After allowing 5 to 34 weeks for expression, we performed conventional and widefield two-photon imaging of layers 2/3, 4 and 5 of the primary visual cortex. We found reproducible trial-by-trial neural responses and tuning properties consistent with known feature selectivity in the visual cortex. Thus, intravenous injection of AAV-PHP.eB does not interfere with the normal processing in neural circuits. In vivo and histological images show no nuclear expression of jGCaMP7s for at least 34 weeks post-injection.